Side-Chain Dynamics Are Critical for Water Permeation through Aquaporin-1 - Smolin, Nikolai (The Biophysical Society, 2008)
Molecular dynamics simulations of aquaporin-1 embedded in a solvated lipid bilayer were carried out to investigate the mechanism of water permeation. The 2.2 Å resolution crystal structure of the bovine protein was used for five independent trajectories. During the equilibration and preparatory steps in which the protein was held fixed, water molecules inside the water channel adopted the same positions as observed in the crystal structure but they did not pass through the channel, suggesting that the dynamic motion of the protein is critical for water permeation. When the protein atoms were allowed to move, the side chains of the two asparagines in the two conserved Asn-Pro-Ala motifs near the center of the channel formed hydrogen bonds with water and helped water molecules move through the channel by actively aligning them for transport. The main-chain oxygen atoms, which were exposed to the pore surface in the crystal structure, also contributed to water transfer. Besides the constriction region observed in the crystal structure (Arg(197), Phe(58), His(182), and Cys(191)), we found that His(76) and Val(155) act as a valve by dynamically blocking water permeation and helping control flow.